Heat Transfer To Fiber Suspensions - Studies Of Particle Characterization And Fouling And Corrosion Mitigation / Ghulamullah Khan - Ghulamullah , Khan (2018)

(untitled)
Fibre suspension heat transfer and frictional pressure drop aspects were usually done in order to characterize fibres while flowing through a pipe lines. Fibre flow behaviour in pipe lines strongly depends on the fiber charateteristics like concentration, properties and suspension flow velocity. Moreover, fibre suspension flow is most significant scientific aspect paerticularly in the pulp and paper industry in such equipment as pipes, pumps, screens, washers etc. Many of them are well known, but still there is some lack of scientific research data regardign to the heat transfer and fricitonal losses to fibre suspensions and this is the major thrust of the current research reported in this thesis. A special conventional flow loop system with externally mounted heaters clamped on the outside of the pipe test section was constructed in order to measure the primarily heat transfer and frictional pressure drop to wood pulp. Fibre characterisation studies were examined employing various types of chemical and mechanical pulp fibre with the emphasis on three types of the one species of accasia mangium and accasia mangium hybrid. Heat trasfer coefficient hc values under the turbulent flow conditiosn, and all data were taken at different velocities and concentrations and at constant heat flux, similarly frictional pressure drops ΔP/L were aslo obtained simultaneously. The results show that most fibre dimensions and paper property data could be correlated with both hc and ΔP/L. The magnitude of hc and ΔP/L were found to depend on flow velocity, fibre concentration, flocculation, fibre population, fibre length, flexibility, coarseness, fibre surface topography, and the amount of fibrillar fines. Due to adhesive and hydrophilic nature of natural fibre, particularly at a lower flow rates, the accumulation of fibre at inner metallic wall surface cause stains and lead to metallic corrosion at particular fibre concnetration and may lead the fouling corosion as well. Alloys of iron epically mild steel and carbon steel are reactive materials and susceptible to corrosion process. The appliation of organic or environmental friendly inhibitor is one of the most widely used and effective industrial technique for the protection of metals against corrosion and in different aggressive mediums due to the advantages of their environmentally friendly, biodegradable in nature and can be synthesized by simple procedure with low cost. This study investigated the effect of environmental friendly additives as Schiff Bases and Gelatin for the mitigation of both fouling and corrosion. These additives comprises electronegative heteroatoms as Nitrogen, Oxygen and Sulfur atoms, different functional groups like -OCH3, -OH, -NO2 and Glutamic acid are responsible to make these additivves as excellent corrosion and fouling inhibitors. The objective of the present research work was to investigate heat trasfer coefficent hc and fricitonal pressure losses for different fibre sepicies as well as corrosion and fouling mechanim to the aggressive and fouling solutions and their mitigation by the application of environmental friendly additives.